2015
DOI: 10.1080/21553769.2015.1041188
|View full text |Cite
|
Sign up to set email alerts
|

Cultivable bacterial diversity and amylase production in two typical light-flavor Daqus of Chinese spirits

Abstract: Culture-dependent methods and molecular techniques were used to simultaneously investigate the cultivable bacterial diversity and amylase production in two typical light- lus amyloliquefaciens). All of the bacterial isolates from the Hongxing Daqu could produce extracellular α-amylase with a maximum yield of 25.3 U/ml by B. cereus H17, whereas B. licheniformis H55 could produce a maximum glucoamylase yield of 41.6 U/ml. Some of the bacterial isolates from the Niulanshan Daqu could also produce extracellular α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 15 publications
(25 reference statements)
1
15
0
Order By: Relevance
“…Secondly, Riesling can grow well in rocks and foggy conditions, which we called an extreme-environment. Bacillus may play a key role during alcohol fermentation [24]. Leveau [23] found that Massilia was the dominant genus on Chardonnay, in our study, it was found that the Massilia in Syr was 8.62%, while in Cha it was just 0.50%.…”
Section: Bacterial and Fungal Taxa Distribution In The Grape Carposphsupporting
confidence: 46%
“…Secondly, Riesling can grow well in rocks and foggy conditions, which we called an extreme-environment. Bacillus may play a key role during alcohol fermentation [24]. Leveau [23] found that Massilia was the dominant genus on Chardonnay, in our study, it was found that the Massilia in Syr was 8.62%, while in Cha it was just 0.50%.…”
Section: Bacterial and Fungal Taxa Distribution In The Grape Carposphsupporting
confidence: 46%
“…Furthermore, comparison of the microbial communities in soil, leaf, and grape samples showed that the main phyla and genera were present in all ecosystems, but in different amounts (Figures 2 and 4), whereas others were sample-specific. For example, in this study, it was found that Pseudomonas and Bacillus existed in both grapes and soil (West et al 2010;Compant et al 2011), certain Pseudomonas species associated exclusively with leaves and other Pseudomonas were found more frequently on grape berries (Leveau and Tech 2011), whilst Bacillus may play a key role during alcohol fermentation (Li et al 2015). Cluster analysis defined generally two major groups: (1) microbial communities on the leaves and grapes, and (2) those originating from the soil.…”
Section: Discussionmentioning
confidence: 59%
“…[20,30,32] Interestingly, Thermomucor, which has been found in Daqu in only a few studies, can secrete large amounts of various hydrolyzing enzymes, including protease, glucosidase, glucoamylase, lipase, and pectinase, which can decompose macromolecules. [28,[33][34][35][36][37][38][39] Thermomucor is therefore expected to be an important contributor to the saccharification and liquefication activities and to cause small metabolites and volatile compounds to be produced during Baijiu production.…”
Section: Prokaryote Community Structure and Diversitymentioning
confidence: 99%